Best Practices for Engaging Underserved Populations. (September 2017) - Stonewall, Jacklin; Fjelstad, Katherine; Dorneich, Michael; Shenk, Linda; Krejci, Caroline; Passe, Ulrike
This work developed and applied a set of "best practices" when engaging marginalized populations to collect data, attitudes, and opinions around a research topic. To support city stakeholders making decisions to create more sustainable and equitable cities, data-driven simulation models are being developed. To ensure that these models are equitable, the needs of marginalized populations must be included. The challenge, however, in understanding these needs is that researchers have often struggled to reach and engage underserved populations. The best practices were developed by reviewing the literature from areas such as psychology, communication, and community planning. These best practices (Earn Trust Through Partnership, Be Multilingual & Inclusive, Communicate for Understanding, Respect Work Schedules and Cultural Norms, and Offer Something Useful) were then applied to the design of a data collection exercise for the study of weatherization decision making and behaviors of urban residents in an economically disadvantaged community. The results of the process were positive with high levels of participation and engagement. The use of the best practices allowed the researchers to better engage with the population, to the benefit of both groups. The development of these best practices will aid researchers in better engaging underserved populations across many areas of study.